Study on Mechanical Characteristics of Nanoclay Reinforced Polymer Composites. (2017) - Shettar, Manjunath; Achutha Kini, U; Sharma, SS; Hiremath, Pavan
Abstract: The present work is focused on analysis and influence of nanoclay on the mechanical behavior of polymers viz., epoxy and polyester. Different types of nanocomposites are prepared using 5 wt% and 10 wt% nanoclay with 95 wt% and 90 wt% epoxy and polyester respectively. Nanoclay is mixed with the resin using a mechanical stirrer for 2 hours to ensure the proper distribution of the reinforcement. Casting technique is used to prepare the specimens according to ASTM standard. The specimens are tested for tensile strength and hardness. 5 wt% of nanoclay increased the tensile strength of resins, but 10 wt% decreased the tensile strength. Hardness value of epoxy resin increased by increasing the wt% of nanoclay, whereas there is no much change in the hardness value of the polyester resin.